(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the analysis of the work being done in our country to improve the quality of education, which is becoming the demand of the time, its goals, achievements and changes in this field were highlighted.